Qur’anic Stories: God, Revelation and the Audience (by Leyla Ozgur Alhassen) - Bruce Lawrence (American Journal of Islam and Society, 2022)
This monograph is an impressive addition to the growing number of studies on the Qur’an as a literary text. The declared focus is not on theology but on theography. To quote Jack Miles, who introduced the term theography: “While theology typically uses the difficult tools of philosophy, theography gravitates toward the more user-friendly and descriptive tools of literary appreciation and, to a point, even towards the tool of biography. Rather than attempt to state the significance of the divine character in philosophical terms, theography aspires more modestly to meet him in the same simple way that characters can be met on the pages of a work of literary art” [God in the Qur’an (New York: Alfred A. Knopf, 2018), 17].